The pension commitments under the rules accounting internacionacionales (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The objective of IAS 19 (International Accounting Standard 19) is to prescribe the accounting and disclosure for “employee benefits” (that is, all forms of considerationgiven by an entity in exchange for service rendered by employees). The principle underlying all of the detailed requirements of this Standard is that the cost of providing employee benefits should be recognised in the period in which the benefitis earned by the employee, rather than when it is paid or payable. The Standard identifies five categories of employee benefits: short-term employee benefits, postemploymentbenefits, other long-term employee benefits, termination benefits andprofit-sharing payments.
Keywords: Employee benefits; short-term employee benefits; post-employment benefits; defined contribution plans; defined benefit plans; other long-term employee benefits; termination benefits; present value of a defined benefit obligation; current service cost; int